Culture reinventing the social sciences - Smith, Mark J. 1962- (Open Univ. Press, 2000)
This introduction to the concept of culture examines the ways in which we approach social enquiry, and argues that cultural theory can help to overcome problems in disciplinary and interdisciplinary analysis.
Keywords: Culture; Cultuur; Kulturtheorie; Kultur